Early childhood teachers’ learning and professional development - Luís, Helena (2017)
This investigation focuses on the construction and foundations of early childhood educators’ personal practical theories, the transformation of these theories (in the first year after the initial training period and ten years after the end of initial training), and the identification of the factors that were involved in and influenced the construction and modification of these theories – in particular, training, supervision, and professional socialization. By means of a small scale qualitative study with a longitudinal perspective, we held two semi-structured interviews with each of the four participants in two stages of the investigation and a Stimulated Recall Interview (Meijer, Zanting, & Verloop, 2002) that was based on observed and recorded video lessons in the final practice of teacher training. The study made it possible to know the contents of the teachers’ practical theories at two different stages of professional development. We can say that the training program (2002–2006) significantly influenced the beliefs and the practical knowledge of educators about how they can organize the teaching learning process of children in a pre-school context. The dimensions in which these influences were most visible were in the organization of the teaching-learning process centred on the child's learning perspective, recognizing his abilities, and giving stimuli to think, communicate, and act. These strategies have been expanded throughout the professional development period – from strategies focused on science education to various dimensions of the everyday life of children, as routines, and the organization of the educational environment (space, time, group organization) as a learning space.